PENDIDIKAN KARAKTER PEDULI LINGKUNGAN DALAM PERSPEKTIF QUR’AN DAN HADITS - Ridlwan, Burhanuddin; Syamsuddin (EL-Islam, 2021)
Abstract: An environment is a place where living things live and all of the surrounding nature. The environment can be defined as a system of interactions between living things and other living things, and between living things and the surrounding environment. The purpose of the interaction is to maintain the sustainability of life itself, then the interaction must be in the form of interaction with balance, harmony, and harmony with the natural environment. Humans as the center of interaction between creatures and the surrounding nature must avoid interactions that damage, exploit, and harm the lives of other creatures, and for their natural environment. The importance of environmental care character education aims to make a person aware of the importance of environmental sustainability, as well as spiritual and religious values, the theme of this research is environmental care character education in the perspective of the Qur'an and hadith, and the focus of this research: first: character education, second: character education caring for the environment, third: understanding the Quran and hadith, fourth: character education caring for the environment in the perspective of the Quran and hadith. The research method used is library research or literary study, which is a study carried out to solve a problem based on a critical and in-depth study of relevant library materials in accordance with the focus of the research. The results of this study, First: That character education is: an active effort in order to form a habit (habit) of a value, Second: That character education cares for the environment is: a process in which a person is expected to acquire environmental awareness, knowledge, skills, values experience and determination that enables them to act collectively or individually in solving environmental problems. Third: That the meaning of the Quran is: kalamullah which was revealed from lauhil Mahfudz to the prophet Muhammad s.a.w., through the intermediary of the angel Gabriel, which is written in the manuscripts. and hadith are something that comes from the prophet Muhammad s.a.w in the form of words, deeds, confessions, and strong desires (hammiyyah), as well as the characteristics of the prophet s.a.w. Fourth: That Character Education Cares for the Environment in the perspective of Al-Quran and Hadith: It is divided into three main areas: 1. The importance of environmental cleanliness, 2. Using the natural environment wisely 3. Maintaining or preserving the natural environment.